Healing Las Vegas : The Las Vegas Community Healing Garden in response to the 1 October tragedy - McAleer, Donna, 1952-; Evans, Stefani (Book collections on Project MUSE., 2019)
"In the aftermath of October 1 tragedy, the Las Vegas community developed a unique response to the pain of those--locals and global visitors to our city--who lost family and friends and the thousands left traumatized by the shooting. The story of the Las Vegas Community Healing Garden is told in the pictures and words of the survivors, volunteers, and local community members who helped create a place of hope, love and compassion. These memories were captured in oral histories over the months since the tragedy"--